Configuration of the Galician Urban Political Elites in Franco’s Dictatorship First Years (1936-1951) - Presas Sobrado, Adrián (Hispania Nova, 2021)
This paper shows that the configuration of the urban political elites in seven Spanish cities in Franco’s dictatorship was produced because of the use of non-experienced in politics men. The study of the continuity and discontinuity of these local elites in the long term, demonstrates that the historiographical idea about the maintenance of a political system which continued with the political culture of classical patronage along the Borbonic Restoration, or just recovering of the Spanish right political culture, can be discussed. The objective of this paper is opening a discussion about historiographical theories which are well established in the Spanish academia.
Keywords: francoism; spanish historiography; elites; political culture; patronage